LESSONS LEARNED FROM THE 2011 GREAT EAST JAPAN EARTHQUAKE TRIGGERED TSUNAMI - Abdullah Yaslam Al-Mashgari, Hafedh (IRC, 2016)
This paper focuses on two mega natural disasters that occurred in Asia: the Great East Japan Earthquake (GEJE) in March of 2011 and the Indian Ocean tsunami of 26th December 2004. This project aimed at studying the success and fail mitigation measure during the disaster. In each disaster, the disaster risk management is investigated and analyzed based on some previous research papers. This project identified the problems of existing systems in the GEJE case, especially problems in urban planning for high-risk areas. Furthermore it gauged the level of awareness of the affected communities with regards to the disaster management practice in preparing themselves for future calamities subsequent to the tsunami disaster of 2004. Based on this research, the lessons to be learned from the two unprecedented disaster occurred in Asia are pointed out.